Hydrophobic solid acid, its preparation method and application
Patent Information
- Application Number
- CN202611444737.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-17
- Publication Date
- 2026-10-30
AI Technical Summary
疏水性固体酸及其制备方法和应用,用以解决传统固体酸催化剂稳定性差、反应效率低的技术问题
(1)本发明通过梯度碳化与分级孔道构建提高了固体酸催化剂的催化效率;分段梯度升温工艺通过控制热解速率形成微孔-介孔-大孔的梯级孔道网络。该结构使炭层比表面积大幅提升,能够负载高负载量的SO42-,为底物分子提供高效扩散通道。
Smart Images

Figure CN122999269A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of esterification reaction catalyst synthesis technology, specifically relating to a hydrophobic solid acid, its preparation method, and its application. Background Technology
[0002] Currently, acid catalysis is an important class of reactions. Early acid catalysts were mainly liquid acids, including hydrochloric acid, sulfuric acid, phosphoric acid, and nitric acid. These liquid acid catalysts have revealed many problems in industrial production: catalyst separation is difficult, they cannot be recycled, they corrode production equipment, the waste liquid generated causes environmental pollution, and the selectivity in the catalytic process is relatively poor. Compared to traditional liquid acid catalysts, solid acid catalysts have become an important development direction in the field of acid catalysis due to their non-toxicity, good environmental compatibility, non-corrosiveness to equipment, and high catalytic selectivity. Solid acid catalysts such as zeolites, ion exchange resins, and heteropoly acids have been extensively studied, but these catalysts also have drawbacks, such as the small size and low conversion rate of zeolites, the high cost of ion exchange resins, and the tendency of heteropoly acids to form a liquid phase system during the reaction, making them difficult to recover.
[0003] For example, KISS AA et al. used H-ZSM-5, Y, and Beta molecular sieve catalysts, achieving a laurate conversion rate of approximately 40% under conditions of an alcohol / acid molar ratio of 1, a catalyst dosage of 3% (mass fraction), a reaction temperature of 130 °C, and a reaction time of 2 h. This may be because the smaller pore size of the zeolite hinders the diffusion of larger reactant molecules, causing the catalytic reaction to mainly occur on the outer surface of the catalyst, thus resulting in a less than ideal catalytic effect. Oliveira et al. used H3PW... 12 O 40 ZrO2 catalyst was used in the esterification reaction of oleic acid and ethanol. Under the conditions of reaction temperature 100℃, oleic acid / ethanol molar ratio 1 / 6, and catalyst dosage 10%, the conversion rate of oleic acid reached 88% after 4 h of reaction. The resulting H3PW... 12 O 40 The ZrO2 catalyst was cleaned with ethanol and dried at 100°C and reused. After four cycles, the catalytic activity decreased significantly, and the conversion rate of oleic acid dropped to about 20%. This may be due to the loss of heteropoly acids, which are more easily soluble in polar solvents.
[0004] Carbon-based solid acid catalysts are inexpensive and readily available, and can effectively reduce SO4 content. 2- Solid acid catalysts have become a research hotspot due to their advantages such as high loading capacity, good catalytic performance, and low corrosion to equipment. However, existing solid acid catalysts have poor tolerance to aqueous environments. Once attacked by water molecules, the surface acid centers will be deactivated, and the reaction performance will decline. Summary of the Invention
[0005] To overcome the shortcomings of the existing technology, the present invention aims to provide a hydrophobic solid acid, its preparation method, and its application. Since the preparation cost of hydrophobic carbon-based solid acids is high, combining them with traditional liquid acids can not only reduce the corrosion and separation costs of pure liquid acids but also avoid the problem of excessively high costs associated with using solid acids. This allows for their application in dehydration fields such as esterification reactions. The hydrophobic solid acid, its preparation method, and its application address the technical problems of poor stability and low reaction efficiency of traditional solid acid catalysts. The present invention selects octadecyltrifluorosilane (OTS) as a modifier to perform hydrophobic modification on the surface of the solid acid catalyst, thereby improving the catalyst's stability.
[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows: A method for preparing a hydrophobic solid acid includes a support and hydrophobic OTS groups on the surface of the support. The support comprises a metal oxide core and a porous carbon layer encapsulating the core, wherein SO4 is distributed within the pores of the porous carbon layer. 2- Specifically, it includes the following steps: (1) Preparation of M x O y @C: M x O y Add the mixture of anhydrous ethanol, pure water, and ammonia to a solution, stir until homogeneous, then add the carbon source solution dropwise, stir thoroughly, and finally dry and carbonize to obtain M. x O y @C particles; (2) Preparation of M x O y @C-SO4 2- : in the M x O y @C particles were sulfonated with concentrated sulfuric acid, and the mixture was then slowly poured into water. The sample was separated and washed with water until no SO4 was found. 2- Until dried, obtain M x O y @C-SO4 2- ; (3) Preparation of M x O y @C-SO4 2- -OTS: Impregnate with SO4 2- The subsequent carrier M x O y @C-SO4 2- Place in OTS solution, dry, and obtain hydrophobic carbonic acid M. x O y @C-SO4 2- -OTS.
[0007] Preferably, in step (1), M x O y The concentration of M is 0.02 g / ml, and the concentration of the carbon source solution is 0.1 g / ml. x O y The mass ratio of carbon source to carbon source is 1:2 to 1:4.
[0008] Preferably, in step (1), the carbon source is one of citric acid, sucrose, glucose, and starch, M x O y It is one of aluminum oxide, cerium oxide, titanium oxide, and iron oxide.
[0009] Preferably, in step (1), the drying temperature is 80~100 ℃ and the drying time is 2~3 h.
[0010] Preferably, in step (1), the carbonization temperature is increased in a segmented gradient: first, the temperature is increased to 300-400 ℃ at 4-6 ℃ / min and held for 4-6 h, then the temperature is increased to 450-500 ℃ at 2-4 ℃ / min and held for 2-3 h, and finally the temperature is increased to 590-610 ℃ at 3-6 ℃ / min and held for 10-12 h.
[0011] Preferably, in step (2), M is... x O y After the @C particles are ground into powder, they are sulfonated with 98% concentrated sulfuric acid solution at a ratio of 1 g: 25~35 ml at 150~165 ℃ for 10~12 h.
[0012] Preferably, in step (2), after the sulfonation reaction is completed, the filtered product is washed with deionized water until neutral and dried at 100 °C for 2-3 h.
[0013] Preferably, in step (3), the concentration of the OTS solution is 0.02~0.16 g / mL; the mass of the OTS is related to the mass of M after the sulfonation reaction. x O y @C-SO4 2- The mass ratio of the powder is 0.1 to 1:1.
[0014] Hydrophobic carbonic acid M x O y @C-SO4 2- -OTS, surface microstructure characteristics are, with M x O y With the core as the core, and stepped porous carbon as the M x O y The protective layer can prevent M x O y Agglomeration, and the use of tiered porous carbon as a carrier facilitates sulfonation, and the functional groups on the carbon layer surface can react with SO4.2- The method forms strong chemical bonds, resulting in catalysts with high stability. It also solves the problem of difficult catalyst recovery. By using OTS to hydrophobically modify the surface of the magnetic carbon layer, the -OH groups on the surface of the OTS and the porous carbon layer are consumed in the condensation reaction. The OTS then bonds with the porous carbon layer through chemical bonds, successfully coating the surface of the porous carbon layer with a low surface energy organic monomolecular film. This prevents water from damaging the acid active sites during esterification reactions, thus improving catalyst stability. This modification method can also be extended to other dehydration reactions, such as amination and dehydration of higher alcohols.
[0015] M x O y @C-SO4 2- -OTS acid is used as a catalyst and mixed with liquid acid catalyst at a mass ratio of 9:1-7:3 in an esterification reaction system. The liquid acid is one or more of sulfuric acid, p-toluenesulfonic acid, and methanesulfonic acid.
[0016] Preferred, M x O y @C-SO4 2- -OTS acid and liquid acid catalyst are combined for the direct esterification reaction of organic acid and polyol. The organic acid is acrylic acid, and the polyol is one of isooctanol, lauryl alcohol, n-octadecyl alcohol, 1,4-butanediol, 1,6-hexanediol, and neopentyl glycol. The organic acid, polyol, polymerization inhibitor, azeotropic agent and reaction gas are mixed evenly in the esterification reactor to carry out the esterification reaction. The reaction gas is generated by the bubble generator at the bottom of the esterification reactor.
[0017] The bubble generator is a microscale gas generator. The reaction gas is N2 or an oxygen-containing nitrogen gas. The esterification reaction is carried out under the following conditions: reaction temperature of 80~110℃, acid-alcohol molar ratio of 1.05~3:1, polymerization inhibitor added at 0.1%~1% of the mass of acrylic acid, and catalyst added at 2.5%~10% of the total mass of acid and alcohol. The crude product is separated into the final product after passing through the separation unit.
[0018] The beneficial effects of this invention are: (1) This invention improves the catalytic efficiency of solid acid catalysts through gradient carbonization and hierarchical pore construction; the segmented gradient heating process forms a microporous-mesoporous-macroporous ladder network by controlling the pyrolysis rate. This structure significantly increases the specific surface area of the carbon layer, enabling it to support high loading of SO4. 2- This provides an efficient diffusion channel for substrate molecules.
[0019] (2) The catalyst has a metal oxide core and a stepped porous carbon as the M core. x O y The protective layer can prevent Mx O y Agglomeration, and the use of tiered porous carbon as a carrier facilitates sulfonation, and the functional groups on the carbon layer surface can react with SO4. 2- The catalysts prepared by forming strong chemical bonds exhibit high stability.
[0020] (3) This method uses OTS to hydrophobically modify the surface of the magnetic carbon layer. During the condensation reaction, the -OH groups of the OTS and the porous carbon layer are consumed, and the OTS and the porous carbon layer are chemically bonded together, successfully covering the surface of the porous carbon layer with a low surface energy organic monomolecular film. This prevents water from destroying the acid active sites in the esterification reaction and improves the stability of the catalyst. The preparation method of this invention is simple and has excellent catalytic performance. It can not only easily achieve solid-liquid separation of the catalyst, but also recycle it, improving the utilization rate of resources, reducing the generation of waste in the production process, and improving the safety of the reaction process. It is a green and environmentally friendly process route.
[0021] (4) In the esterification reaction process, the gas generator at the bottom of the esterification reactor provides micron-level nitrogen or air, which not only inhibits polymerization but also increases the probability of intermolecular collisions between acids and alcohols. When acrylic acid and polyols undergo esterification, the alcohol feed sprayer can control the dripping rate of the polyol, which is beneficial for the reaction to proceed towards the target product diester and inhibits the formation of the by-product monoester. The monoester product separated from the distillation column can be recycled back to the esterification reactor for further reaction. The reaction not only inhibits the formation of monoester but also further promotes the formation of diester. At the same time, the dehydration membrane is a molecular sieve type dehydration membrane, which can efficiently remove moisture from the product. Attached Figure Description
[0022] Figure 1 This is a schematic diagram of the process of the present invention.
[0023] 1-Esterification reactor, 2-Bubble generator, 3-Water separator, 4-Water washing tower, 5-Alkali washing tower, 6-Salt washing tower, 7-Distillation tower, 8-Alcohol feed sprayer, 9-Dehydration membrane. Detailed Implementation
[0024] The present invention will be further described in detail below with reference to the embodiments.
[0025] Example 1 A hydrophobic carbon-based acidic Al2O3@C-SO4 2- The preparation method of the -OTS catalyst includes the following steps: (1) Preparation of Al2O3@C: Take 100 mL of a mixture of 0.02 g / mL Al2O3 anhydrous ethanol-pure water-ammonia water (volume ratio of 3:1:1) and stir for 30 min until the system is uniformly dispersed; add 40 mL of 0.1 g / mL citric acid solution (mass ratio of Al2O3 to carbon source of 1:2) dropwise and continue stirring for 2 h until fully mixed. Place the mixture in an 80 ℃ oven to dry for 3 h, and then transfer it to a tube furnace for segmented gradient carbonization: raise the temperature to 300 ℃ at 4 ℃ / min and hold for 6 h; raise the temperature to 450 ℃ at 2 ℃ / min and hold for 3 h; finally raise the temperature to 590 ℃ at 3 ℃ / min and hold for 12 h, and obtain Al2O3@C particles after natural cooling.
[0026] (2) Preparation of Al2O3@C-SO4² - The Al2O3@C particles obtained in step (1) were ground into 100-mesh powder. 2 g of this powder was mixed with 60 mL of 98% concentrated sulfuric acid (solid-liquid ratio 1 g:30 mL) and sulfonated in an oil bath at 150 ℃ for 12 h. After sulfonation, the mixture was slowly poured into 200 mL of ice water, stirred to disperse, and then filtered to separate the solid sample. The filtered product was repeatedly washed with deionized water until no SO4²⁻ was found in the washing liquid. - (No white precipitate was formed when tested with barium chloride solution). The sample was then dried in a 100 ℃ oven for 2 h to obtain Al2O3@C-SO4². - powder.
[0027] (3) Preparation of Al2O3@C-SO4² - -OTS: Take 1 g of Al2O3@C-SO4² obtained in step (2). - Add 5 mL of 0.02 g / mL OTS solution (OTS and Al2O3@C-SO4²) to the powder. - After impregnation for 30 min (mass ratio 0.1:1), the mixture was dried in an oven at 80 ℃ for 4 h, cooled, and then ground until homogeneous to obtain Al2O3@C-SO4². - -OTS composite material.
[0028] The catalyst in this embodiment has a BET specific surface area of 216 m² / g, a macropore diameter of 63 nm, a mesopore diameter of 31 nm, a micropore diameter of 1.5 nm, and a water contact angle of 120°, according to the test results.
[0029] The catalytic performance of the obtained catalyst and liquid acid was tested in five esterification reactions according to the specified mixing ratios. The reaction of acrylic acid with monohydric alcohols used an alcohol-acid molar ratio of 1.05:1, while the reaction of acrylic acid with dihydric alcohols used an acid-alcohol molar ratio of 3:1. The catalyst dosage was 1.5% of the total mass of the acid and alcohol, and the reaction pressure was atmospheric pressure. After the reaction, the reaction solution was cooled and filtered to remove the catalyst. The product composition was analyzed by gas chromatography (GC) using a TR-WAX polar capillary column (30 m × 0.25 mm × 0.25 μm) and a flame ionization detector (FID). The product yield was calculated using the area normalization method. Specific reaction conditions are as follows: Reaction System 1: This reaction uses acrylic acid and 1,4-butanediol as raw materials to synthesize 1,4-butanediol diacrylate. The reaction temperature is 110℃, and the alcohol-acid molar ratio is controlled at 3:1. After the reaction is complete, the yield of 1,4-butanediol diacrylate is determined by gas chromatography.
[0030] Reaction System 2: This reaction uses acrylic acid and isobutanol as raw materials to synthesize isobutyl acrylate. The reaction temperature is 110℃, and the alcohol-acid molar ratio is controlled at 1.05:1. After the reaction is complete, the yield of isobutyl acrylate is determined by gas chromatography.
[0031] Reaction System 3: This reaction uses acrylic acid and isooctanol (2-ethylhexanol) as raw materials to synthesize isooctyl acrylate. The reaction temperature is 110℃, and the alcohol-acid molar ratio is controlled at 1.05:1. After the reaction is complete, the yield of isooctyl acrylate is determined by gas chromatography.
[0032] Reaction System 4: This reaction uses acrylic acid and 1,6-hexanediol as raw materials to synthesize 1,6-hexanediol diacrylate. The reaction temperature is 110℃, and the alcohol-acid molar ratio is controlled at 3:1. After the reaction is complete, the yield of 1,6-hexanediol diacrylate is determined by gas chromatography.
[0033] Reaction System 5: This reaction uses acrylic acid and neopentyl glycol as raw materials to synthesize neopentyl glycol diacrylate. The reaction temperature is 110℃, and the alcohol-acid molar ratio is controlled at 3:1. After the reaction is complete, the yield of neopentyl glycol diacrylate is determined by gas chromatography.
[0034] Of the five esterification reactions, the yields of 1,4-butanediol diacrylate were 92%, isobutyl acrylate was 91%, isooctyl acrylate was 90%, 1,6-hexanediol diacrylate was 89%, and neopentyl glycol diacrylate was 90%.
[0035] Example 2 A hydrophobic carbon-based acidic CeO2@C-SO4 2- The preparation method of the -OTS catalyst includes the following steps: (1) Preparation of CeO2@C: Take 100 mL of a mixture of 0.02 g / mL CeO2 anhydrous ethanol-pure water-ammonia water (volume ratio of 3:1:1) and stir for 30 min until the system is uniformly dispersed; add 60 mL of 0.1 g / mL sucrose solution (CeO2 to carbon source mass ratio of 1:3) dropwise and continue stirring for 2 h until fully mixed. Place the mixture in a 90 ℃ oven to dry for 2.5 h, and then transfer it to a tube furnace for segmented gradient carbonization: raise the temperature to 350 ℃ at 5 ℃ / min and hold for 5 h; raise the temperature to 480 ℃ at 3 ℃ / min and hold for 2.5 h; finally raise the temperature to 600 ℃ at 4 ℃ / min and hold for 12 h, and obtain CeO2@C particles after natural cooling.
[0036] (2) Preparation of CeO2@C-SO4² - The CeO2@C particles obtained in step (1) were ground into 100-mesh powder. 2 g of this powder was mixed with 50 mL of 98% concentrated sulfuric acid (solid-liquid ratio 1 g: 25 mL) and sulfonated in an oil bath at 155 ℃ for 10 h. After sulfonation, the mixture was slowly poured into 200 mL of ice water, stirred to disperse, and then filtered to separate the solid sample. The filtered product was repeatedly washed with deionized water until no SO4²⁻ was found in the washing liquid. - It was then dried in an oven at 100 ℃ for 3 h to obtain CeO2@C-SO4² - powder.
[0037] (3) Preparation of CeO2@C-SO4² - -OTS: Take 1 g of CeO2@C-SO4² obtained in step (2). - Add 5 mL of 0.06 g / mL OTS solution (OTS and CeO2@C-SO4²) to the powder. - After impregnation for 30 min (mass ratio 0.3:1), the mixture was dried in an oven at 80 ℃ for 4 h, cooled, and then ground until homogeneous to obtain CeO2@C-SO4². - -OTS composite material.
[0038] The catalyst in this embodiment has a BET specific surface area of 209 m² / g, a macropore diameter of 71 nm, a mesopore diameter of 28 nm, a micropore diameter of 1.6 nm, and a water contact angle of 117°, according to the test results.
[0039] Of the five esterification reactions, the yields of 1,4-butanediol diacrylate were 94%, isobutyl acrylate was 89%, isooctyl acrylate was 91%, 1,6-hexanediol diacrylate was 93%, and neopentyl glycol diacrylate was 91%.
[0040] Example 3 A hydrophobic carbon-based acidic TiO2@C-SO4 2- The preparation method of the -OTS catalyst includes the following steps: (1) Preparation of TiO2@C: Take 100 mL of a mixture of 0.02 g / mL TiO2 anhydrous ethanol-pure water-ammonia water (volume ratio of 3:1:1) and stir for 30 min until the system is uniformly dispersed; add 80 mL of 0.1 g / mL glucose solution (TiO2 to carbon source mass ratio of 1:4) dropwise and continue stirring for 2 h until fully mixed. Place the mixture in a 100 ℃ oven to dry for 2 h, and then transfer it to a tube furnace for segmented gradient carbonization: heat up to 400 ℃ at 6 ℃ / min and hold for 4 h; then heat up to 500 ℃ at 4 ℃ / min and hold for 2 h; finally heat up to 610 ℃ at 6 ℃ / min and hold for 10 h, and obtain TiO2@C particles after natural cooling.
[0041] (2) Preparation of TiO2@C-SO4² - The TiO2@C particles obtained in step (1) were ground into 100-mesh powder. 2 g of this powder was mixed with 70 mL of 98% concentrated sulfuric acid (solid-liquid ratio 1 g:35 mL) and sulfonated in a 165 ℃ oil bath for 10 h. After sulfonation, the mixture was slowly poured into 200 mL of ice water, stirred to disperse, and then filtered to separate the solid sample. The filtered product was repeatedly washed with deionized water until no SO4²⁻ was found in the washing liquid. - It was then dried in an oven at 100 ℃ for 3 h to obtain TiO2@C-SO4² - powder.
[0042] (3) Preparation of TiO2@C-SO4² - -OTS: Take 1 g of TiO2@C-SO4² obtained in step (2). - Add 5 mL of 0.10 g / mL OTS solution (OTS and TiO2@C-SO4²) to the powder. - (Mass ratio 0.5:1), after impregnation for 30 min, it is dried in an oven at 80 ℃ for 4 h, cooled and ground evenly to obtain TiO2@C-SO4². - -OTS composite material.
[0043] The catalyst in this embodiment has a BET specific surface area of 213 m² / g, a macropore diameter of 67 nm, a mesopore diameter of 31 nm, a micropore diameter of 1.2 nm, and a water contact angle of 124°, according to the test results.
[0044] Of the five esterification reactions, the yields of 1,4-butanediol diacrylate were 95%, isobutyl acrylate was 93%, isooctyl acrylate was 92%, 1,6-hexanediol diacrylate was 95%, and neopentyl glycol diacrylate was 93%.
[0045] Example 4 A hydrophobic carbon-based acidic Fe3O4@C-SO4 2- The preparation method of the -OTS catalyst includes the following steps: (1) Preparation of Fe3O4@C: Take 100 mL of a mixture of 0.02 g / mL Fe3O4 anhydrous ethanol-pure water-ammonia water (volume ratio 3:1:1) and stir for 30 min until the system is uniformly dispersed; add 60 mL of 0.1 g / mL citric acid solution (total mass ratio of Fe3O4 to carbon source 1:3) dropwise and continue stirring for 2 h until fully mixed. Place the mixture in a 90 ℃ oven to dry for 2.5 h, and then transfer it to a tube furnace for segmented gradient carbonization: raise the temperature to 350 ℃ at 5 ℃ / min and hold for 5 h; raise the temperature to 480 ℃ at 3 ℃ / min and hold for 2.5 h; finally raise the temperature to 600 ℃ at 5 ℃ / min and hold for 11 h, and obtain Fe3O4@C particles after natural cooling.
[0046] (2) Preparation of Fe3O4@C-SO4² - The Fe3O4@C particles obtained in step (1) were ground into 100-mesh powder. 2 g of this powder was mixed with 60 mL of 98% concentrated sulfuric acid (solid-liquid ratio 1 g:30 mL) and sulfonated in a 160 ℃ oil bath for 11 h. After sulfonation, the mixture was slowly poured into 200 mL of ice water, stirred to disperse, and then filtered to separate the solid sample. The filtered product was repeatedly washed with deionized water until no SO4²⁻ was found in the washing liquid. - It was then dried in an oven at 100 °C for 2.5 h to obtain Fe3O4@C-SO4². - powder.
[0047] (3) Preparation of Fe3O4@C-SO4² - -OTS: Take 1 g of Fe3O4@C-SO4² obtained in step (2). - Add 5 mL of 0.12 g / mL OTS solution (OTS and Fe3O4@C-SO4²) to the powder. - (Mass ratio 0.6:1), after impregnation for 30 min, it is dried in an oven at 80 ℃ for 4 h, cooled and ground evenly to obtain Fe3O4@C-SO4². - -OTS composite material.
[0048] The catalyst in this embodiment has a BET specific surface area of 209 m² / g, a macropore diameter of 59 nm, a mesopore diameter of 28 nm, a micropore diameter of 1.3 nm, and a water contact angle of 118°, according to the test results.
[0049] Of the five esterification reactions, the yields of 1,4-butanediol diacrylate were 96%, isobutyl acrylate was 91%, isooctyl acrylate was 96%, 1,6-hexanediol diacrylate was 92%, and neopentyl glycol diacrylate was 91%.
[0050] Comparative Example 1 A carbon-based acidic Fe3O4@C-SO4 2- The method for preparing the catalyst includes the following steps: (1) Preparation of Fe3O4@C: Take 100 mL of a mixture of 0.02 g / mL Fe3O4 anhydrous ethanol-pure water-ammonia water (volume ratio of 3:1:1) and stir for 30 min until the system is uniformly dispersed; add 40 mL of 0.1 g / mL citric acid solution (Fe3O4 to carbon source mass ratio of 1:2) dropwise and continue stirring for 2 h until fully mixed. Place the mixture in an 80 ℃ oven to dry for 3 h, and then transfer it to a tube furnace for segmented gradient carbonization: raise the temperature to 300 ℃ at 4 ℃ / min and hold for 6 h; raise the temperature to 450 ℃ at 2 ℃ / min and hold for 3 h; finally raise the temperature to 590 ℃ at 3 ℃ / min and hold for 12 h, and obtain Fe3O4@C particles after natural cooling.
[0051] (2) Preparation of Fe3O4@C-SO4² - The Fe3O4@C particles obtained in step (1) were ground into 100-mesh powder. 2 g of this powder was mixed with 60 mL of 98% concentrated sulfuric acid (solid-liquid ratio 1 g:30 mL) and sulfonated in a 150 ℃ oil bath for 12 h. After sulfonation, the mixture was slowly poured into 200 mL of ice water, stirred to disperse, and then filtered to separate the solid sample. The filtered product was repeatedly washed with deionized water until no SO4²⁻ was found in the washing liquid. - (No white precipitate was formed when tested with barium chloride solution). The sample was then dried in a 100 ℃ oven for 2 h to obtain Fe3O4@C-SO4². - powder.
[0052] The comparative catalyst was tested and found to have a BET specific surface area of 212 m² / g, a macropore diameter of 61 nm, a mesopore diameter of 33 nm, a micropore diameter of 1.4 nm, and a water contact angle of 73°.
[0053] Of the five esterification reactions, the yields of 1,4-butanediol diacrylate were 87%, isobutyl acrylate was 84%, isooctyl acrylate was 88%, 1,6-hexanediol diacrylate was 89%, and neopentyl glycol diacrylate was 82%.
[0054] Comparative Example 2 A carbon-based acidic CeO2@C-SO4 2- The method for preparing the catalyst includes the following steps: (1) Preparation of CeO2@C: Take 100 mL of a mixture of 0.02 g / mL CeO2 anhydrous ethanol-pure water-ammonia water (volume ratio of 3:1:1) and stir for 30 min until the system is uniformly dispersed; add 60 mL of 0.1 g / mL sucrose solution (CeO2 to carbon source mass ratio of 1:3) dropwise and continue stirring for 2 h until fully mixed. Place the mixture in a 90 ℃ oven to dry for 2.5 h, and then transfer it to a tube furnace for segmented gradient carbonization: raise the temperature to 350 ℃ at 5 ℃ / min and hold for 5 h; raise the temperature to 480 ℃ at 3 ℃ / min and hold for 2.5 h; finally raise the temperature to 600 ℃ at 4 ℃ / min and hold for 12 h, and obtain CeO2@C particles after natural cooling.
[0055] (2) Preparation of CeO2@C-SO4² - The CeO2@C particles obtained in step (1) were ground into 100-mesh powder. 2 g of this powder was mixed with 50 mL of 98% concentrated sulfuric acid (solid-liquid ratio 1 g: 25 mL) and sulfonated in an oil bath at 155 ℃ for 10 h. After sulfonation, the mixture was slowly poured into 200 mL of ice water, stirred to disperse, and then filtered to separate the solid sample. The filtered product was repeatedly washed with deionized water until no SO4²⁻ was found in the washing liquid. - It was then dried in an oven at 100 ℃ for 3 h to obtain CeO2@C-SO4² - powder.
[0056] According to the test results, the catalyst in this embodiment has a BET specific surface area of 201 m² / g, a macropore diameter of 63 nm, a mesopore diameter of 25 nm, a micropore diameter of 1.2 nm, and a water contact angle of 69°.
[0057] Of the five esterification reactions, the yields of 1,4-butanediol diacrylate were 87%, isobutyl acrylate was 76%, isooctyl acrylate was 82%, 1,6-hexanediol diacrylate was 81%, and neopentyl glycol diacrylate was 83%.
[0058] Comparative Example 3 A carbon-based acidic TiO2@C-SO4 2-The method for preparing the catalyst includes the following steps: (1) Preparation of TiO2@C: Take 100 mL of a mixture of 0.02 g / mL TiO2 anhydrous ethanol-pure water-ammonia water (volume ratio of 3:1:1) and stir for 30 min until the system is uniformly dispersed; add 80 mL of 0.1 g / mL glucose solution (TiO2 to carbon source mass ratio of 1:4) dropwise and continue stirring for 2 h until fully mixed. Place the mixture in a 100 ℃ oven to dry for 2 h, and then transfer it to a tube furnace for segmented gradient carbonization: heat up to 400 ℃ at 6 ℃ / min and hold for 4 h; then heat up to 500 ℃ at 4 ℃ / min and hold for 2 h; finally heat up to 610 ℃ at 6 ℃ / min and hold for 10 h, and obtain TiO2@C particles after natural cooling.
[0059] (2) Preparation of TiO2@C-SO4² - The TiO2@C particles obtained in step (1) were ground into 100-mesh powder. 2 g of this powder was mixed with 70 mL of 98% concentrated sulfuric acid (solid-liquid ratio 1 g:35 mL) and sulfonated in a 165 ℃ oil bath for 10 h. After sulfonation, the mixture was slowly poured into 200 mL of ice water, stirred to disperse, and then filtered to separate the solid sample. The filtered product was repeatedly washed with deionized water until no SO4²⁻ was found in the washing liquid. - It was then dried in an oven at 100 ℃ for 3 h to obtain TiO2@C-SO4² - powder.
[0060] The catalyst in this embodiment has a BET specific surface area of 202 m² / g, a macropore diameter of 56 nm, a mesopore diameter of 36 nm, a micropore diameter of 1.1 nm, and a water contact angle of 73°, according to the test results.
[0061] Of the five esterification reactions, the yields of 1,4-butanediol diacrylate were 83%, isobutyl acrylate was 86%, isooctyl acrylate was 84%, 1,6-hexanediol diacrylate was 87%, and neopentyl glycol diacrylate was 84%.
[0062] Comparative Example 4 A carbon-based magnetic acidic Fe3O4@C-SO4 2- The method for preparing the catalyst includes the following steps: (1) Preparation of Fe3O4@C: Take 100 mL of a mixture of 0.02 g / mL Fe3O4 anhydrous ethanol-pure water-ammonia water (volume ratio 3:1:1) and stir for 30 min until the system is uniformly dispersed; add 60 mL of 0.1 g / mL citric acid solution (total mass ratio of Fe3O4 to carbon source 1:3) dropwise and continue stirring for 2 h until fully mixed. Place the mixture in a 90 ℃ oven to dry for 2.5 h, and then transfer it to a tube furnace for segmented gradient carbonization: raise the temperature to 350 ℃ at 5 ℃ / min and hold for 5 h; raise the temperature to 480 ℃ at 3 ℃ / min and hold for 2.5 h; finally raise the temperature to 600 ℃ at 5 ℃ / min and hold for 11 h, and obtain Fe3O4@C particles after natural cooling.
[0063] (2) Preparation of Fe3O4@C-SO4² - The Fe3O4@C particles obtained in step (1) were ground into 100-mesh powder. 2 g of this powder was mixed with 60 mL of 98% concentrated sulfuric acid (solid-liquid ratio 1 g:30 mL) and sulfonated in a 160 ℃ oil bath for 11 h. After sulfonation, the mixture was slowly poured into 200 mL of ice water, stirred to disperse, and then filtered to separate the solid sample. The filtered product was repeatedly washed with deionized water until no SO4²⁻ was found in the washing liquid. - It was then dried in an oven at 100 °C for 2.5 h to obtain Fe3O4@C-SO4². - powder.
[0064] The catalyst in this embodiment has a BET specific surface area of 201 m² / g, a macropore diameter of 55 nm, a mesopore diameter of 31 nm, a micropore diameter of 1.8 nm, and a water contact angle of 68°, according to the test results.
[0065] Of the five esterification reactions, the yields of 1,4-butanediol diacrylate were 81%, isobutyl acrylate was 79%, isooctyl acrylate was 84%, 1,6-hexanediol diacrylate was 79%, and neopentyl glycol diacrylate was 82%.
[0066] M x O y @C-SO4 2- -OTS acid is used as a catalyst and mixed with liquid acid catalyst at a mass ratio of 9:1-7:3 in an esterification reaction system. The liquid acid is one or more of sulfuric acid, p-toluenesulfonic acid, and methanesulfonic acid.
[0067] Preferred, M x O y @C-SO4 2--OTS acid and liquid acid catalyst are combined for the direct esterification reaction of organic acid and polyol. The organic acid is acrylic acid, and the polyol is one of isooctanol, lauryl alcohol, n-octadecyl alcohol, 1,4-butanediol, 1,6-hexanediol, and neopentyl glycol. The organic acid, polyol, polymerization inhibitor, azeotropic agent and reaction gas are mixed evenly in the esterification reactor to carry out the esterification reaction. The reaction gas is generated by the bubble generator at the bottom of the esterification reactor.
[0068] The bubble generator is a microscale gas generator. The reaction gas is N2 or an oxygen-containing nitrogen gas. The esterification reaction is carried out under the following conditions: reaction temperature of 80~110℃, acid-alcohol molar ratio of 1.05~3:1, polymerization inhibitor added at 0.1%~1% of the mass of acrylic acid, and catalyst added at 2.5%~10% of the total mass of acid and alcohol. The crude product is separated into the final product after passing through the separation unit.
[0069] The esterification reaction process flow diagram is attached. Figure 1 As shown in the diagram, the process mainly consists of a reaction unit and a separation and purification unit. The reaction unit mainly includes an esterification reactor 1 and a water separator 3, while the separation and purification unit mainly includes a water washing tower 4, an alkali washing tower 5, a salt washing tower 6, and a distillation tower 7. The bubble generator 2 at the bottom of the esterification reactor 1 provides micron-level nitrogen or oxygen-containing nitrogen gas for the reaction. The crude ester product undergoes water washing, alkali washing, salt washing, and distillation, and the final product enters the finished product tank.
[0070] The outlet of bubble generator 2 is connected to water washing tower 4, the top outlet of water washing tower 4 is connected to alkali washing tower 5, the top outlet of alkali washing tower 5 is connected to salt washing tower 6, the top outlet of salt washing tower 6 is connected to distillation tower 7, and the outlet of distillation tower 7 is connected to esterification reactor 1 in a loop. A water distribution tower 3 is installed above the esterification reactor 1, and the esterification reactor 1 and the water distribution tower 3 are connected in a loop.
[0071] Nitrogen or oxygen-containing nitrogen is introduced into the bottom of the bubble generator 2.
[0072] An alcohol feed sprayer 8 is installed on the top of the esterification reactor 1.
[0073] A dehydration membrane 9 is installed at the top of the alkali washing tower 5.
[0074] Preferably, in the esterification reaction of acrylic acid and diol to form a diester, the alcohol feed sprayer can control the dripping rate of the polyol, which is conducive to the reaction proceeding toward the target product diester and inhibits the formation of the by-product monoester.
[0075] Preferably, in the esterification reaction of acrylic acid and diol to form a diester, the monoester product separated by the distillation column 7 can be recycled to the esterification reactor 1 to continue the reaction. The reaction can not only inhibit the formation of monoester, but also further promote the formation of diester product.
[0076] Preferably, the dehydration membrane 9 is a molecular sieve type dehydration membrane, which can efficiently remove moisture from the product.
[0077] This invention discloses a hydrophobic carbon-based acidic M x O y @C-SO4 2- - A method for preparing OTS catalysts. The catalytic efficiency of solid acid catalysts is improved through gradient carbonization and hierarchical pore construction, which not only significantly increases the specific surface area of the carbon layer but also enables the loading of high amounts of SO4. 2- This provides an efficient diffusion channel for substrate molecules. The catalyst uses M... x O y With the core as the core, and stepped porous carbon as the M x O y The protective layer can prevent M x O y Agglomeration, and the use of tiered porous carbon as a carrier facilitates sulfonation, and the functional groups on the carbon layer surface can react with SO4. 2- The method forms strong chemical bonds, resulting in a catalyst with high stability. It also solves the problem of difficult catalyst recovery, is environmentally friendly, and has great application prospects and promotional value. This method uses OTS to hydrophobically modify the surface of a magnetic carbon layer. During the condensation reaction, the -OH groups on the surface of the porous carbon layer are consumed, and the OTS and porous carbon layer are chemically bonded, successfully coating the surface of the porous carbon layer with a low surface energy organic monomolecular film. This prevents water from destroying the acid active centers in the esterification reaction, improving catalyst stability. Furthermore, the introduction of a bubble generator into the esterification process not only inhibits polymerization but also increases the collision probability of acid and alcohol molecules. An alcohol feed sprayer and monoester circulation promote the formation of acrylate diester.
[0078] The above content is only for illustrating the technical concept of the present invention and should not be construed as limiting the scope of protection of the present invention. Any modifications made to the technical solution based on the technical concept proposed in this invention shall fall within the scope of protection of the claims of this invention.
Claims
1. A method for preparing a hydrophobic solid acid, characterized in that, Specifically, the following steps are included: (1) M x O y Add the mixture of anhydrous ethanol, pure water, and ammonia to a solution, stir until homogeneous, then add the carbon source solution dropwise, stir thoroughly, and finally dry and carbonize to obtain M. x O y @C particles; (2) In the M x O y @C particles were sulfonated with concentrated sulfuric acid, and the mixture was then slowly poured into water. The sample was separated and washed with water until no SO4 was found. 2- Until dried, obtain M x O y @C-SO4 2- ; (3) Impregnate with SO4 2- The subsequent carrier M x O y @C-SO4 2- Place in OTS solution, dry, and you will get a hydrophobic solid acid, namely hydrophobic carbonyl acid M. x O y @C-SO4 2- -OTS.
2. The method for preparing a hydrophobic solid acid according to claim 1, characterized in that, In step (1), M x O y The concentration of M is 0.02 g / ml, and the concentration of the carbon source solution is 0.1 g / ml. x O y The mass ratio of carbon source to carbon source is 1:2 to 1:4; In step (1), the carbon source is one of citric acid, sucrose, glucose, or starch, M x O y It is one of aluminum oxide, cerium oxide, titanium oxide, and iron oxide.
3. The method for preparing a hydrophobic solid acid according to claim 1, characterized in that, In step (1), the drying temperature is 80~100 ℃ and the drying time is 2~3 h; The carbonization temperature is increased in stages: first, the temperature is increased to 300-400℃ at a rate of 4-6℃ / min and held for 4-6 hours; then, the temperature is increased to 450-500℃ at a rate of 2-4℃ / min and held for 2-3 hours; finally, the temperature is increased to 590-610℃ at a rate of 3-6℃ / min and held for 10-12 hours.
4. The method for preparing a hydrophobic solid acid according to claim 1, characterized in that, In step (2), M x O y After the @C particles are ground into powder, they are sulfonated with 98% concentrated sulfuric acid solution at a ratio of 1 g: 25~35 ml at 150~165 ℃ for 10~12 h.
5. The method for preparing a hydrophobic solid acid according to claim 1, characterized in that, In step (2), after the sulfonation reaction is completed, the filtered product is washed with deionized water until neutral and dried at 100 °C for 2-3 h.
6. The method for preparing a hydrophobic solid acid according to claim 1, characterized in that, In step (3), the concentration of the OTS solution is 0.02~0.16 g / mL; the mass of the OTS is related to the mass of M after the sulfonation reaction. x O y @C-SO4 2- The mass ratio of the powder is 0.1 to 1:
1.
7. The hydrophobic carbonyl acid M prepared by the method according to any one of claims 1-6 x O y @C-SO4 2- -OTS, characterized in that, With M x O y With the core as the core, and stepped porous carbon as the M x O y The protective layer consists of a low surface energy organic monomolecular film covering the surface of the tiered porous carbon layer.
8. M prepared based on the method according to any one of claims 1-6 x O y @C-SO4 2- The application of -OTS acid is characterized by... M x O y @C-SO4 2- -OTS acid is used as a catalyst and mixed with liquid acid catalyst at a mass ratio of 9:1-7:3, and applied in esterification reaction system.
9. The M according to claim 8 x O y @C-SO4 2- The application of -OTS acid is characterized by... The liquid acid catalyst is one or more of sulfuric acid, p-toluenesulfonic acid, and methanesulfonic acid; M x O y @C-SO4 2- -OTS acid and sulfonic acid catalyst are combined and applied to the direct esterification reaction of organic acid and polyol. The organic acid is acrylic acid and the polyol is one of isooctyl alcohol, lauryl alcohol, n-octadecyl alcohol, 1,4-butanediol, 1,6-hexanediol and neopentyl glycol. The organic acid, polyol, polymerization inhibitor, azeotropic agent and reaction gas are mixed evenly in the esterification reactor (1) to carry out the esterification reaction. The reaction gas is generated by the bubble generator (2) at the bottom of the esterification reactor (1).
10. The M according to claim 9 x O y @C-SO4 2- The application of -OTS acid is characterized by... The bubble generator (2) is a microscale gas generator. The reaction gas is N2 or a type of oxygen-containing nitrogen gas. The esterification reaction is carried out under the following conditions: reaction temperature is 80~110℃, acid-alcohol molar ratio is 1.05~3:1, the amount of polymerization inhibitor added is 0.1%~1% of the mass of acrylic acid, and the amount of catalyst added is 2.5%~10% of the total mass of acid and alcohol. The crude product is separated into the final product after passing through the separation unit.
